Benthic marine invertebrate herbivores diversify their algal diets in winter - R. M. Yoshioka; A. W. E. Galloway; J. B. Schram; L. E. Bell; K. J. Kroeker (Ecosphere)
Abstract Changes in the seasonal environment substantially influence organisms. Understanding how species respond to such changes, such as in their feeding interactions and physiology, is key to predicting their resilience to both seasonal and longer term climate changes. The Sitka Sound in Southeast Alaska, USA, is an attractive natural laboratory for studying change, as the marine environment experiences substantial seasonal fluctuations in parameters such as temperature, pH, and productivity between summer and winter. By sampling a suite of dominant macrophyte algae and their benthic herbivores in winter (January) and summer (July) 2019, we investigated how producers and their primary consumers may respond to seasonal change inferred through fatty acid trophic markers. We used a fatty acid logratio selection and analysis approach to ask the following: (1) Do fatty acid biomarkers for algae differ between seasons? (2) Do the same fatty acid biomarkers differ between seasons when applied to herbivores, with herbivore fatty acids tracking the presumed trophic resources? (3) Do fatty acid biomarkers for herbivores differ between seasons, when considered independently from algae? Comparing logratio sets selected each for the algae and the herbivore fatty acids, we found that algae fatty acids were different between our sampling seasons, but the algae‐selected fatty acid logratios did not clearly separate most herbivores by season. In contrast, the herbivore‐selected logratios strongly distinguished herbivore species between the January and June samplings. Further, dispersions of fatty acid logratios were greater within herbivore species in the winter than in the summer, potentially due to the utilization of more diverse resources when preferred algae are less abundant. In total, results suggest that herbivores are not simply tracking the seasonal fatty acid changes in the dominant algae as trophic resources; instead, herbivore fatty acid seasonal changes may occur largely through some other nonexclusive mechanisms, such as omnivory, reductions or shifts in dietary composition, and/or endogenous physiological responses. Thus, the benthic herbivores in our study appear not to be locked into their diets when faced with seasonal change and may use a range of strategies, including diet diversification, to cope with environmental variation.